Teaching activities for improving reading skills in second B.G.U students at Integración Técnica Educativa High School during the school year 2017-2018 - Camacho Salazar, Ivonne Jazmín (2019)
The goal of this research was to propose teaching activities to improve the reading skills in Second B.G.U students at Integración Técnica Educativa High School during the school year 2017 – 2018. The population of this study consisted of 30 students of 2nd year BGU and 2 English teachers. This study was theoretical since it was supported by a conceptual framework, it was also exploratory, and was focused on qualitative and quantitative methods. The proposal was carried out during 5 weeks, from November 5th to December 7th 2018……..